DABCOnium: An Efficient and High‐Voltage Stable Singlet Oxygen Quencher for Metal–O2 Cells. Issue 20 (9th April 2019) - Petit, Yann K.; Leypold, Christian; Mahne, Nika; Mourad, Eléonore; Schafzahl, Lukas; Slugovc, Christian; Borisov, Sergey M.; Freunberger, Stefan A.
Abstract: Singlet oxygen ( 1 O2 ) causes a major fraction of the parasitic chemistry during the cycling of non‐aqueous alkali metal‐O2 batteries and also contributes to interfacial reactivity of transition‐metal oxide intercalation compounds. We introduce DABCOnium, the mono alkylated form of 1, 4‐diazabicyclo[2.2.2]octane (DABCO), as an efficient 1 O2 quencher with an unusually high oxidative stability of ca. 4.2 V vs. Li/Li + . Previous quenchers are strongly Lewis basic amines with too low oxidative stability. DABCOnium is an ionic liquid, non‐volatile, highly soluble in the electrolyte, stable against superoxide and peroxide, and compatible with lithium metal. The electrochemical stability covers the required range for metal–O2 batteries and greatly reduces 1 O2 related parasitic chemistry as demonstrated for the Li–O2 cell. Abstract : Serving quench : Singlet oxygen ( 1 O2 ) formation deleteriously affects the cycling stability of many alkali cathodes, such as the Li–O2 cathode. An efficient and high‐voltage stable 1 O2 quencher results in greatly reduced 1 O2 related side reactions. Quenchers stable under high‐voltage are relevant to control 1 O2 related interfacial reactivity and long‐term cyclability of many cathodes.